2019
DOI: 10.1111/nmo.13745
|View full text |Cite
|
Sign up to set email alerts
|

Colonic neuronal loss and delayed motility induced by high‐fat diet occur independently of changes in the major groups of microbiota in Swiss mice

Abstract: The prevalence of obesity is a public health concern, and evidence links obesity to the development of chronic diseases, such as diabetes, cancer, and diseases of the cardiovascular and nervous systems. 1 Obesity has also been associated with gastrointestinal motility disorders 2 ; constipation and longer colonic transit times are frequently observed in animal models of excessive fat intake in the diet. 3,4 Normal intestinal motility involves the coordinated function of extrinsic innervation of the intestine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…HFD‐induced neuroplasticity also seems to be characterized by specific enteric neuron subpopulations being targeted. Previous studies have shown a decrease in the density of nitrergic, cholinergic, and vasoactive intestinal peptide (VIP)‐ergic neurons 14,19,32,36,39,40 . These findings may help to explain the mechanisms involved in the impaired motility observed in this model with excitatory and inhibitory motoneurons with acetylcholine, and VIP and NO as primary neurotransmitters, respectively 44 .…”
Section: Ens Cells Are Modulated By Hfdssupporting
confidence: 58%
See 2 more Smart Citations
“…HFD‐induced neuroplasticity also seems to be characterized by specific enteric neuron subpopulations being targeted. Previous studies have shown a decrease in the density of nitrergic, cholinergic, and vasoactive intestinal peptide (VIP)‐ergic neurons 14,19,32,36,39,40 . These findings may help to explain the mechanisms involved in the impaired motility observed in this model with excitatory and inhibitory motoneurons with acetylcholine, and VIP and NO as primary neurotransmitters, respectively 44 .…”
Section: Ens Cells Are Modulated By Hfdssupporting
confidence: 58%
“…Myenteric neurons directly control motility and are among the most affected enteric neural cells in the HFD model (Table 1). Increasing data suggest that different HFD interventions, independent of percentages and duration, can promote changes that may result in myenteric neuronal loss 32–34,36,39–41 …”
Section: Ens Cells Are Modulated By Hfdsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, minimal studies have evaluated the impact of dietary intake on constipation from the perspective of its integrated effects, such as total energy loads, which were mainly supplied by the metabolism of protein, carbohydrate, and fat ingested by us every day. A few pieces of literature have shown that inappropriate intake of macronutrients like a high-fat diet may disturb gastrointestinal motility, suggesting that high energy intake may do as well ( 10 13 ). Therefore, we hypothesize that high energy intake may correlate with a higher risk of chronic constipation.…”
Section: Introductionmentioning
confidence: 99%
“…While neurons are not energy-storing cells and their use of fatty acids as an energy source is minimal, they do contain LD [20]. High fat diet causes obesity and loss of myenteric neurons in Swiss mice [21].…”
Section: Introductionmentioning
confidence: 99%